An Expanded Servicescape Framework as the Driver of Place Attachment and Word of Mouth. (March 2018) - Line, Nathaniel D.; Hanks, Lydia; Kim, Woo Gon
The purpose of this study is to identify the effects of other customers on consumption behavior in shared consumption environments. The proposition is put forth that, like other factors that make up the consumption atmosphere, the mere presence of other customers has a significant impact on customers' attachment to service organizations. Accordingly, this research proposes a framework that specifies the nature of the relationships among customer homogeneity in the social servicescape, company identification, place attachment, and word-of-mouth referral. To test the hypotheses, data were collected from a sample of 1, 094 restaurant patrons in the United States. Results of structural equation analyses supported the overall contention that, in addition to the traditionally identified aspects of the servicescape (e.g., facility attractiveness, ambient conditions, seating comfort, and layout), the mere presence of others can affect the extent to which individuals perceive feelings of attachment to the restaurant. This relationship is demonstrated to take place via the mediating effect of company identification.